Public Perception of Multiple VAT Rates in Nepal: An Analytical Study - Kunwar, Keshar Bahadur (Journal of Tikapur Multiple Campus, 2026)
The aim of this research is to investigate the perspectives of taxpayers, traders, experts, and consumers on the implementation of multiple VAT rates in Nepal's tax system. This study investigates how individuals in Nepal perceive multiple Value Added Tax (VAT) rates. This study employs a unique and descriptive approach with data from 120 participants from the different field, including tax officials, experts, traders, and consumers. Multiple VAT rates are intended to eliminate cascade effects, improve transparency, increase revenue mobilization and broaden the tax base. However, respondents expressed worries about stability, and numerous major points were made regarding the complexity and cost of managing multiple VAT rates. All alternative hypotheses were accepted at significant levels of significance, and the statistical analysis validated the significance of these impressions. The results are helpful for policymakers trying to balance Nepal's VAT system's administrative viability, efficiency, and transparency.